Symbolic Meanings In The Road Not Taken Poetry By Robert Frost - Martina Girsang; Lio Naomi Situmorang; Dona Chrystina Situngkir; Imanuela Elpride; Yemima Vrianita Simangunsong (Departement of Mathematics Education, 2023)
Each symbol that exist in every poetry has its significant depth meaning that not everyone can casually understand. Although, poetry is one of the oldest forms of literature that exits, and its rhyme and symbols that deliver to indicate every further meaning that needed for. This study will try to deliver the symbolizes that exist in one of poetry created by Robert Frost, entitled The Road not Taken. This masterpiece has indicated a depth meaning that none could easily allocated, even understands by only managing to read the poetry only once. The collected data will be based on to find the symbols in the poetry, The Road not Taken by Robert Frost and the source of the data will be taken based on the same titled literary work. The writer will writes down every stanzas of the literary work then afterwards the writer will tries to describe every part of the stanzas meaning based on how the symbol exist in the poetry. Robert Frost is one of poet that significantly managed to use symbols in most of his works. By allocating the symbols into the literary work, one can find the depth meaning of every word in the stanza of the said work, to understand more to the fullest. The Road not Taken had gives certain impact which allows readers to understand that we have to thoroughly and deeply choose what kind of path we like to walk into to. Every part of certain poetry has their significant symbols that managed to utter the meaning of the said poetry. Poetry has brought significant gift thorough humanity’s life, as one artwork that only exist within contained beautiful words that formed based on only language.